Saúde bucal como temática para um ensino de química contextualizado - Trevisan, Marcele Cantarelli (2012)
This research paper presents a study of the teaching and learning process of some Chemistry contents through the use of the theme Oral Health, developing a contextualized teaching of Chemistry. Oral Health is an essential component for many biological functions of human beings, such as chewing, swallowing and speaking, being directly linked to the quality of life of the people. Therefore, through this study, it was attempted to investigate actions that facilitate the apprenticeship in Chemistry and that contribute to the civic education of the students. In order to do this, it was applied a series of interventions in a Junior class in a public school in Santa Maria, RS. As the textbooks are the main source of information for teachers to prepare their lessons, it was analyzed the main textbooks used in Chemistry teaching in the city of Santa Maria in relation to the thematic approach of Oral Health. In order to characterize the subjects and to investigate the prior knowledge of the students about the theme, it was applied an initial questionnaire that served to guide the development of the six interventions applied in the classroom. Through the instruments of evaluation used, it can be noticed that the contextualization during the chemistry classes, using the theme Oral Health, contributes to the improvement of the teaching and learning process and promoted the civic education of the students.